The politics of autism : navigating the contested spectrum - Pitney, John J., Jr., 1955- (Rowman & Littlefield, 2015)
"In this first book devoted exclusively to the contentious politics of autism, noted political scientist and public policy expert John J. Pitney, Jr., explains how autism has evolved into a heated political issue disputed by scientists, educators, social workers, and families."--Jacket